Education, employment and practice: Midwifery graduates in Papua New Guinea. (October 2016) - Moores, Alison; Puawe, Paula; Buasi, Nancy; West, Florence; Samor, Mary K.; Joseph, Nina; Rumsey, Michele; Dawson, Angela; Homer, Caroline S.E.
Abstract: Background: Papua New Guinea has a very high maternal mortality rate (773/100, 000), low rates of supervised births and a critical shortage of skilled midwives. A midwifery education initiative commenced in 2012, funded by the Australian Government and led by the National Department of Health. One specific objective of the initiative was to improve the standard of clinical teaching and practice in four schools of midwifery. There were 394 midwives educated over the 4 year period (2012–2015) representing half of all midwives in Papua New Guinea. A study was undertaken to describe the educational programme, employment, practices and experiences of graduates who studied midwifery in 2012 and 2013 as part of the initiative. Objective: the aim of this paper is to explore the education, employment and practice of newly graduated midwives in Papua New Guinea. Design: a mixed methods descriptive study design was used. Surveys and focus groups were used to gather data. Ethical approval was granted by the relevant Human Research Ethics Committees. Setting and participants: all midwifery graduates in 2012 and 2013 from the four midwifery schools in Papua New Guinea were included in the study and almost 80% were contacted. Findings: nearly 90% of graduates were working as midwives, with an additional 3% working as midwifery or nursing educators. This study discovered that graduates exhibited increased skills acquisition and confidence, leadership in maternal and newborn care services and a marked improvement in the provision of respectful care to women. The graduates faced challenges to implement evidence based care with barriers including the lack of appropriate resources and differences of opinion with senior staff. Conclusions: factors affecting the quality of midwifery education will need to be addressed if Papua New Guinea is to continue to improve the status of maternal and newborn health. Specifically, the length of the midwifery education, the quality of clinical practice and the exposure to rural and remote area practice need addressing in many contexts like Papua New Guinea. Highlights: 90% of graduates are working as midwives and 3% working as educators. Emergency Obstetric and Neonatal Skills were the most valued by graduates. Graduates reported increased skills acquisition, confidence and leadership. A significant improvement in the provision of respectful care to women. Improvements needed include the length of the course, the quality of clinical practice and experiences in rural areas.